The Effect Of Autoclaved – Cooled Jack Bean (Canavalia Ensiformis (L.) Dc.) High RS-4 Starch On Lowering Glucose Level And Characteristics Of Digesta Of Stz-Na Induced Type-2 Diabetes Mellitus Rats - Azkia Nastiti; Agnes Murdiati; Y. Marsono (Indonesian Association of Food Technologists, 2017)
Jack bean is one of local beans known to contain natural resistant starch (RS) content. To increase its RS content, four cycle autoclaving – cooling treatment modification was applied to generate resistant starch type 4 (RS-4) which refers to RS obtained from modification. RS is able to improve blood glucose level of diabetic individuals. This research aimed to measure the effect of jack bean autoclaved – cooled starch (AC starch) diet on blood glucose level and digesta characteristics of type-2 diabetic Sprague Dawley rats in vivo. Bioassay analyses showed that jack bean AC starch consumption decreased blood glucose level at range of 96.05mg/dl – 135.97mg/dl. The diet was also able to increase short chain fatty acids (SCFA) production in form of acetic acid, propionic acid, and butiric acid, to increase total weight and moisture content of digesta, while reduce digesta pH, as well as to inhibit glucose absorption. Diet of 50% high RS jack bean AC starch showed the best results in all glucose metabolism parameters for type-2 diabetic animals.